2019
DOI: 10.1093/ptj/pzz145
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Success for Student Physical Therapists on the National Physical Therapy Examination: Systematic Review and Meta-Analysis

Abstract: Background In physical therapist education, the National Physical Therapy Examination (NPTE) is the predominant measure of student success. Because the NPTE is a high-stakes examination, predicting NPTE performance is important for physical therapist students and programs. Purpose The purpose of this study was to determine the relationships between first-attempt NPTE performance and physical therapist applicant variables and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
68
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(71 citation statements)
references
References 37 publications
2
68
1
Order By: Relevance
“…However, reports have indicated that on average between 3.6-9.9% of students admitted into DPT programs in the United States since 2011 failed to meet the programs' academic standard and did not graduate (Commission on Accreditation in Physical Therapy Education, 2018). While the admission criteria for students entering a DPT program are based upon markers that are suggestive of previous and future academic success, such as undergraduate GPA and GRE scores, the progression from undergraduate studies to a graduate professional DPT program can be daunting (Veld et al, 2018;Wolden et al, 2020). The curricula of United States DPT programs average 88 weeks of didactic work that begins with a combination of foundational and clinical science courses (Commission on Accreditation in Physical Therapy Education, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, reports have indicated that on average between 3.6-9.9% of students admitted into DPT programs in the United States since 2011 failed to meet the programs' academic standard and did not graduate (Commission on Accreditation in Physical Therapy Education, 2018). While the admission criteria for students entering a DPT program are based upon markers that are suggestive of previous and future academic success, such as undergraduate GPA and GRE scores, the progression from undergraduate studies to a graduate professional DPT program can be daunting (Veld et al, 2018;Wolden et al, 2020). The curricula of United States DPT programs average 88 weeks of didactic work that begins with a combination of foundational and clinical science courses (Commission on Accreditation in Physical Therapy Education, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Predictors of successful professional entry for students completing degrees in a range of health professions are known and include discipline understanding, academic skills and standardized test taking ability; students' demographic information is not consistently significantly predictive (Johnson, Purcell, Power, & Cumming, in preparation). For example, predictors for physiotherapy student success on the registration exam in the USA are also known and include: four entry variables (undergraduate overall and prerequisite grade point average (GPA), standardized testing, and admission scores comprising interview and other ratings); and four during-program variables, GPA in years 1 and 3, clinical performance in first and final placements, and comprehensive exam scores (Wolden, Hill, & Voorhees, 2020). It may be that SLP has entry or during-program predictors of outcomes that are similar to those identified in physiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…In rehabilitation science programs, traditionally cognitive factors such as grade point average (GPA) and standardized test scores, have been heavily weighted in admissions decisions [ 1 ] and used for matriculated students to predict academic performance in the didactic curriculum and licensure exam scores [ 2 ]. While these cognitive variables are generally considered good indicators of future academic performance, most studies show that they explain less than half of the variance in academic outcomes for speech-language pathology (SLP) [ 3 ] and physical therapy (PT) [ 4 ] students.…”
Section: Introductionmentioning
confidence: 99%
“…This is partially because “non-cognitive” has been used as an all-encompassing term in the literature to include any factor outside of GPA and standardized test scores [ 9 ]. Some authors consider interviews and/or letters of recommendation under the non-cognitive umbrella [ 10 ]; others include constructs such as critical thinking, clinical reasoning, or reflection [ 2 ]. This broad definition presents a great challenge when attempting to synthesize the literature and draw conclusions.…”
Section: Introductionmentioning
confidence: 99%